«Tutto il colore tiene»: Renato Birolli rilegge Delacroix, Van Gogh, Cézanne (Materiali di Estetica. Terza serie, 2023)
Colour is a central issue in Renato Birolli’s painting and theory since it is discussed by the artist in his writings and diary’s notes starting from the mid-1930s. The article highlights Delacroix, Van Gogh and Cézenne influence in Birolli’s work, discussing his theory of “colour-form”.
Keywords: Renato Birolli; Corrente; Modern Art; Theory of Colour